Transcriptome Sequencing Investigated the Tumor-Related Factors Changes After T. gondii Infection - Lu, Gang; Zhou, Jian; Zhao, Ying hui; Li, Qiao ling; Gao, Yun yun; Wang, Lin (Frontiers in Microbiology, 2019)
T. gondii is an intracellular parasite and causes a global epidemic parasitic disease. T. gondii-infection could inhibit the growth of tumor. In this study, the transcriptomes of samples were detected by deep sequencing analysis. The transcriptome data was compared with reference genome to perform sequence alignment and the further analysis. The analyses of differential expression and the differentially expressed genes were performed in the present study. Genes involved in P53 signaling pathway, COLORECTAL cancer pathway, NON-SMALL CELL LUNG cancer signaling pathway and BREAST cancer signaling pathway were up-regulated or down-regulated among the samples. The KEGG analysis indicated that the cancer pathways changed after infection of T. gondii. Furthermore, tumor-related mRNAs from different samples had a large difference, which suggested that the difference might provide important information in resisting cancer. The protein results indicated that tumor-related protein changes occurred after infection of T. gondii. In conclusion, the infection changed the cancer pathways, which could inhibit the growth of tumor.